К вопросу о применении налоговой амнистии - Ivanenko I. N., Kovalenko E. A., Aleksanian K. A. (Science, education, society: trends and prospects, 2017)
In article questions of application of tax amnesty are considered
Keywords: налоговая амнистия; tax amnesty